Empowering Pre-Service English Foreign Language (EFL) Teachers in Academic Writing and Publishing: Navigating Opportunities and Challenges - Wahyuningsih, Sri (Lectura : Jurnal Pendidikan, 2025)
Despite the growing emphasis on academic writing and publishing in EFL teacher education, limited research has explored how pre-service EFL teachers navigate it. This study addresses this gap by examining the opportunities and challenges faced by pre-service EFL teachers in academic writing and publishing. The study employed a qualitative case study. Through interviews with two pre-service EFL teachers, observation, and documentation, the findings highlight opportunities in academic writing and publishing programs, including enhancing professional competency, fostering critical thinking and communication skills, promoting evidence-based teaching practices, advancing career recognition, and encouraging reflective practice. Equipped with academic writing and publishing skills, pre-service EFL teachers are better prepared to meet the demands of modern classrooms and contribute to the educational field through research and publication. However, participants also faced challenges, such as linguistic and rhetorical difficulties, limited research and critical thinking skills, psychological barriers, and issues related to the publishing process. The study offers practical implications for teacher education programs, emphasizing the need for explicit instruction in academic writing and research methodologies, mentorship, feedback, and support for participation in academic conferences. Furthermore, the findings suggest that institutional culture and academic expectations also influence pre-service teachers’ engagement in scholarly writing. A lack of exposure to real publication practices, limited access to academic journals, and insufficient training in digital literacy were additional concerns. Addressing these factors holistically can significantly enhance teacher candidates’ readiness for academic contribution.